CLINICAL AND LABORATORY PARAMETERS ASSOCIATED WITH DEATH IN ACUTE PANCREATITIS - Spasić, Marko; Janković, Slobodan; Stefanović, Srđan; Kostić, Irena; Radovanović, Dragče; Đorđević, Nataša; Radosavljević, Ivan; Divjak, Ana; Milojević, Anđela; Jelić, Ivana; Čanović, Dragan (Vojnosanitetski pregled, 2017)
Introduction. Acute pancreatitis is an inflammatory condition having the significant mortality rate in the case of severe forms of disease. The aim of this study was to investigate putative factors of increased mortality with contradictory prior evidence, and to reveal previously unexplored factors. Methods. A prospective cohort study with nested case/control design included all adult patients treated for acute pancreatitis in Clinical Center of Kragujevac, Serbia, during the 3-year period (from October 2011 to December 2014). The cases (n=19) were patients who died, while the controls (n=113) were patients who survived. The associations between putative risk factors and the study outcomes were tested by univariate and multivariate logistic regressions, and expressed as crude and adjusted odds ratios (OR) with corresponding 95% confidence intervals (CI). Results. Significant association with the lethal outcome in acute pancreatitis was found for advanced age (adjusted OR 1.12, 95%CI 1.02-1.23), presence of significant comorbidities (adjusted OR 10.62, 95%CI 1.01-111.39), higher interleukin-8 (IL-8) value on third day from onset of symptoms (adjusted OR 1.05, 95%CI 1.02-1.08), use of tramadol and/or morphine (adjusted OR 47.34, 95%CI 3.21-699.08), BISAP score ≥ 3 in the first 24 hours (adjusted OR 48.11, 95%CI 3.14-736.29), and prophylactic use of antibiotics (adjusted OR 0.07, 95%CI 0.01-0.85). Conclusion. Advanced age, significant comorbidities, use of tramadol and/or morphine and more severe disease as assessed by BISAP score can increase the risk for death in acute pancreatitis, while prophylactic use of antibiotics may have a protective role.Key words: acute pancreatitis, mortality, opioid analgesics, IL-8, antibiotic prophylaxis